Remedying "Enforced Sexual Slavery": Validating Victims' Reparation Claims against Japan - Hong, Seong Phil (Journal of East Asia and international law, 2013)
It has been over two decades since the Japanese practice of enforced sexual slavery began to receive widespread attention. Yet despite numerous international efforts to urge Japan to squarely acknowledge its moral and legal responsibility, there has been no meaningful progress to resolve this matter. This work revisits the issue of enforced sexual slavery as it stands today. The Japanese practice of enforced sexual slavery was a clear violation of international law at the time. Therefore, individual victims have valid legal claims for reparation against the Japanese government. The first half of this article reconfirms the illegality of the practice of enforced sexual slavery. The remainder summarizes and vindicates the claims of the victims once again. This research suggests how to remedy the victims’ rights and discusses how to implement reparation. It also contends that Japan owes reparations and legitimate remedial measures to the victims that go beyond monetary compensation in line with the rules of contemporary international law.